Accurate but inefficient: Standard face identity matching tests fail to identify prosopagnosia. (28th January 2022) - Fysh, Matthew C.; Ramon, Meike
Abstract: In recent years, the number of face identity matching tests in circulation has grown considerably and these are being increasingly utilized to study individual differences in face cognition. Although many of these tests were designed for testing typical observers, recent studies have begun to utilize general-purpose tests for studying specific, atypical populations (e.g., super-recognizers and individuals with prosopagnosia). In this study, we examined the capacity of four tests requiring binary face-matching decisions to study individual differences between healthy observers. Uniquely, we used performance of the patient PS (Rossion, 2018), a well-documented case of acquired prosopagnosia (AP), as a benchmark. Two main findings emerged: (i) PS could exhibit typical rates of accuracy in all tests; (ii) compared to age-matched controls and when considering both accuracy and speed to account for potential trade-offs, only the KFMT — but not the EFCT, PICT or GFMT — was able to detect PS's severe impairment. These findings reflect the importance of considering both accuracy and response times to measure individual differences in face matching, and the need for comparing tests in terms of their sensitivity, when used as a measure of human cognition and brain functioning. Highlights: Patient PS completed four tests of face matching: the GFMT and KFMT (short versions); the EFCT; and the PICT. PS exhibited accuracy that was within the normal range on each test. Combining speed and accuracy, only the KFMT discriminated PS from age-matched controls.